Remodeling of intestinal bacterial community and metabolome of Dezhou donkey induced by corn silage - Sha, Yujie; Yu, Jiafeng; Xia, Dong; Zhang, Yan; Liu, Jian; Wang, Huisong (Scientific reports, 2024)
Corn silage can usually improve the growth performance and the meat quality of ruminants, and subsequently increase the economic benefits of farming. However, little is known about the effects of corn silage on donkeys. This experiment investigated the effects of corn silage on the weight gain, gut microbiota and metabolites of Dezhou donkeys. A total of 24 Dezhou donkeys, sourced from the same farm and exhibiting similar age and average body weight, were utilized in this experiment. The donkeys were allocated into two groups: a control group receiving a basic diet and a test group receiving a basic diet supplemented with 30% corn silage. Each group comprised 12 donkeys, evenly distributed by sex (6 males and 6 females). The experiment lasted for 100 days. Results showed that dietary supplementation with corn silage significantly (P < 0.05) improved the weight gain of Dezhou donkeys at the end of the experiment. And the supplementation of corn silage in the diet significantly altered the bacterial community composition and metabolome in the feces of the donkeys. Notably, the relative abundance ratio of Bacteroidetes to Firmicutes was 0.76 in the control group compared to 0.96 in the test group. Furthermore, members of the Bacteroidetes and Firmicutes phyla were associated with differentiated metabolites enriched in the arachidonic acid metabolism and pentose and glucuronate interconversion pathways, both of which have been reported to be related to animal growth. Specifically, Bacteroidia exhibited statistically (P < 0.05) positive correlations with 15S-HpETE, while Bacilli demonstrated statistically (P < 0.05) negative correlations with D-Xylulose. The findings of this study can advance our mechanistic understanding of the remodeling of intestinal microbiota and metabolome induced by corn silage, as well as their relationships with the growth performance of Dezhou donkeys, which in turn favor the improvement in nutrition of Dezhou donkeys.